Solar irrigation in Nepal: Subsidy design, farmer adoption, and utilization patterns - Varshney, Deepak; Mukherji, Aditi; Shrestha, Shisher; Ghimire, Laxman Prasad (2025)
Solar irrigation pumps (SIPs) are central to Nepal’s strategy for sustainable irrigation and reducing reliance on diesel pumps. The Alternative Energy Promotion Centre (AEPC) officially provides a 60% subsidy for SIPs under a demand-driven program. This study assesses (i) SIP subsidy delivery and adoption processes, and (ii) utilization patterns and their drivers, using a household survey of 630 farmers and a phone survey of 404 SIP owners.
In practice, farmers contributed only 4% of total SIP costs on average, as local governments frequently topped up AEPC’s subsidy, making SIPs nearly free. While this boosted affordability, the scheme is only weakly progressive: large farmers also benefit from near-complete subsidization, raising equity and fiscal concerns. The applicant pool is dominated by educated, wealthier, and socially advantaged groups, while marginalized farmers are often excluded due to weak information and institutional gatekeeping. Utilization is moderate, with SIPs operating around 745 hours annually—well below their technical potential. Breakdowns, long repair delays (averaging 110 days), and missing after-sales services reduce use. Training in operation and maintenance increases utilization by 38%, while cultivation of water-intensive crops also drives higher use. Transparent communication of the full subsidy package, progressive cost-sharing to prioritize smallholders, and stronger investment in training and rapid-repair services are essential. Without such reforms, the program risks under-utilization and elite capture of subsidies, undermining SIPs’ transformative potential for agricultural resilience and low-carbon growth.